Protection of Victims of Violent Crime Sexuality in Higher Education Reviewed According to Minister of Education and Culture Regulation Number 30 of 2021 - Ali, Muhammad Ghoffar; Anditya, Ariesta Wibisono (Southeast Asian Journal of Victimology, 2023)
The increasing number of cases of sexual violence that occur in the university environment makes the government, in this case, the Ministry of Education and Culture of the Republic of Indonesia ratify and enforce Ministry of Education and Culture Regulation Number 30 of 2021 concerning the Prevention and Handling of Sexual Violence in Higher Education Environments. The importance of the passing of this regulation is to fill the legal vacuum in terms of handling sexual violence in universities, including the protection of the rights and obligations of victims and perpetrators and the entire academic community, with a definite legal umbrella, it is hoped that it can reduce the criminal act of sexual violence. In addition, Minister of Education and Culture Regulation Number 30 of 2021 not only focuses on punishment and sanctions, but also pays attention to the rights of victims and perpetrators as well as the obligations that must be carried out by universities. Examples of the rights of victims and perpetrators such as; Sustainability guarantees for completing studies, protection of identity confidentiality, provision of information regarding protection facilities, etc. In addition, examples of obligations from universities are; the establishment of a Task Force (SATGAS) that plays an active role in helping prevent and handle cases of sexual violence in the relevant universities.